INSECURITY AND TAX REVENUE GENERATION: AN ASSESSMENT OF ZAMFARA STATE TAX ADMINISTRATION - Maru, Muhammad Lawal Bawa; Abubakar, Mohammed Bello (Kashere Journal of Management Sciences, 2024)
Infrastructural Development depends upon tax revenue; which volume being linked to tax administration strategies. Equally, on the policy stance, tax revenue is directly a function of tax administration; which includes, identification of taxpayers, tax accounting and calculations and tax collection procedures. As tax compliance largely depend upon stable economic activities; which signify valuable tax bases. Thus, economic growth and development to larger extent determine the tax-takes in any economy. To these effects, this study determines the effects of insecurity on revenue generation in Zamfara State within the reviewed period. Time-series data of 2014 to 2021 on monthly tax revenue collection was used and ARIMA Model employed for appropriate forecast. It was found that, the use of Consultant in tax administration has significant impact in tax revenue generation. Equally, indicates that, tax revenue collections significantly respond to economic activities. Therefore, the study concludes that, healthy economic activities which results from the secured society and use of experts (outside personnel) are greatly valuable for tax revenue generation. The study recommends among others that, tax revenue should be returned to the taxpayers through infrastructural development. Public expenditure should be guided by effective income forecast.